1993
DOI: 10.1007/bf02251206
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and sports in patients suffering from Parkinson's disease in comparison with healthy seniors

Abstract: Physical activity during lifetime was investigated among 32 Parkinson patients (age 65.6 +/- 8.1 yrs, mean +/- SD) retrospectively by means of a structured interview. Data were compared with 31 healthy controls (age 61.7 +/- 5.8 yrs). An objective score was obtained by presenting a list of all kinds of sports, subjective estimation of physical activity was done by visual analogous scales. Until the occurrence of the first symptoms (mean = 58.5 yrs) the patients did not differ from controls. During the course o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
42
0
4

Year Published

2006
2006
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 5 publications
1
42
0
4
Order By: Relevance
“…12 Most previous studies of this topic have several potential methodological problems: only one was a prospective study with a nested case-control design, 14 whereas two others included prevalent cases with retrospective assessment of physical activity 12 13 and small sample size. 13 Recently, the findings of a prospective cohort study were published, showing an inverse association with physical activity in men but not in women. 15 The authors suggested that limited power, due to the few cases of Parkinson's disease among women, was the most likely explanation for the difference in effect between the sexes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Most previous studies of this topic have several potential methodological problems: only one was a prospective study with a nested case-control design, 14 whereas two others included prevalent cases with retrospective assessment of physical activity 12 13 and small sample size. 13 Recently, the findings of a prospective cohort study were published, showing an inverse association with physical activity in men but not in women. 15 The authors suggested that limited power, due to the few cases of Parkinson's disease among women, was the most likely explanation for the difference in effect between the sexes.…”
Section: Discussionmentioning
confidence: 99%
“…11 In humans, four previous studies have investigated the role of physical activity in preventing Parkinson's disease. [12][13][14][15] In the only prospective study, men who exercised strenuously had a 60% decreased risk of Parkinson's disease compared with men who did not, but no clear effect was observed in women. 15 To provide additional prospective data, we evaluated the relationship between physical activity and risk of Parkinson's disease in an ongoing study, the Harvard Alumni Health Study.…”
mentioning
confidence: 94%
“…One smaller case-control study (32 cases) reported similar level of physical activity in cases and controls [460], another including a subset of cases with early onset PD reported a decreased risk associated with regular exercise, confined to younger age groups [355]. A case-control study nested within the Harvard College Alumni cohort reported non-significant ORs below unity for engaging in varsity athletics and exercise at the time of college, for usual physical activity such as stair climbing and walking, as well as for practice of sports in adulthood before PD onset [461].…”
Section: Case-control Studiesmentioning
confidence: 93%
“…This is caused by a combination of physical impairments (e.g., walking problems, pain), cognitive dysfunction (e.g., depression, apathy, and dementia), and fatigue. 1 This lack of sufficient mobility is deleterious for PD patients. A scientific statement of the American Heart Association recently underscored that a sedentary lifestyle is one of the leading preventable causes of death, and that an inverse linear relationship exists between volume of physical activity and all-cause mortality.…”
mentioning
confidence: 99%